Clinical and causality assessment in herbal hepatotoxicity. (May 2013) - Teschke, Rolf; Schwarzenboeck, Alexander; Eickhoff, Axel; Frenzel, Christian; Wolff, Albrecht; Schulze, Johannes
<x xml:space="preserve">Abstract</x> Introduction: Herbal hepatotoxicity represents a poorly understood, neglected and multifaceted disease with numerous confounding variables and missing established causality in the majority of cases. This review discusses overt shortcomings in its clinical and causality assessment and suggests improvements. Areas covered: A selective literature search of PubMed using the terms herbal hepatotoxicity, herb-induced liver injury, drug hepatotoxicity and drug-induced liver injury was performed to identify published case reports, spontaneous case reports, case series and review articles regarding hepatotoxicity due to herbs, herbal drugs and herbal dietary supplements. Covered areas focused on confounding variables related to the documentation of the herbal product and the clinical course, hepatotoxicity and reexposure criteria, temporal association, comedication and alternative causes with special attention to preexisting diseases of the liver, bile ducts and the pancreas. Of particular interest were recent discussions of approaches designed and validated for hepatotoxicity causality, such as the scale of CIOMS (Council for International Organizations of Medical Sciences). Expert opinion: The authors call for substantial improvements in data quality of herbal products and case characteristics and strongly recommend using the CIOMS scale to assess causality in suspected herbal hepatotoxicity.